Invaliditatea și dizabilitatea. Interferenţe legislative ale sistemelor de asigurări sociale și asistență socială din România - Felicia Cornelia Macarie; Liliana Somesan (Vitca) (Revista Transilvană de Ştiinţe Administrative, 2019)
The study analyzes the legislative overlaps in the social insurance system and the social assistance system in Romania, and the effects of the competences applied identically from the methodological point of view by the institutions empowered to exercise the medical expertise or evaluation of people with various health or disability problems. The paper also analyzes how the national social assistance system intervenes in a subsidiary or, as the case may be, complementary to social insurance systems as component parts of social security, through the levers of social benefits and social services. The analysis of the current situation of the social security system in Romania shows that for a long time the emphasis was placed on the financial side needed for treatments and medication as a way to alleviate the condition of the invalid or disabled person, but too little attention was paid to the integration of these persons in the life of the society and the use of these human resources as potential generators of surplus value in the family and society. It is possible that these social policies involuntarily accentuate the feeling of worthlessness, social exclusion, inappropriateness alongside stereotypes and prejudices towards people with disabilities that have oscillated over time from marginalization and ignorance to compassion and respect. The legal and procedural framework of social insurance and social assistance are analyzed in correlation with the evolution of the number of beneficiaries and with the main weaknesses of the social security system.